Вплив соціально-психологічного феномену конформізму на прийняття управлінських рішень - Черепаха, М. О. (ХНУРЕ, 2024)
Throughout his life, a person makes certain decisions that affect many aspects of his life. This article examines the influence of conformity on the process of making management decisions. Some situations generate more conformity, others less. Taking into account the conditions necessary to create maximum or, conversely, minimum compliance is the key to creating a successful management process.
Keywords: конформізм; прийняття управлінських рішень